2022
DOI: 10.3390/su14021002
|View full text |Cite
|
Sign up to set email alerts
|

Using Organigraphs to Map Disaster Risk Management Governance in the Field of Cultural Heritage

Abstract: Global cultural heritage is threatened by the increasing frequency and severity of natural disasters caused by climate change. International experts emphasise the importance of managing cultural heritage sustainably as part of a paradigm shift in cultural heritage perception, understanding, and management. This paradigm shift has stimulated a need to integrate cultural heritage into pre-existing disaster risk management governance. However, there is currently a lack of robust and practical approaches to map th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…This issue is found to be addressed by Du et al [49], where map cognition concerning the time-critical perspective is improvised to offer more elaborated visual information in a crisis map. The adoption of organigraphs is discussed by Durrant et al [50] where the authors have stated its significance towards preparedness against. However, the authors also suggested that there is still an enormous scope for improvement, and the existing system is not yet ready for large scale and dynamic situations.…”
Section:  Crisis Mapping Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This issue is found to be addressed by Du et al [49], where map cognition concerning the time-critical perspective is improvised to offer more elaborated visual information in a crisis map. The adoption of organigraphs is discussed by Durrant et al [50] where the authors have stated its significance towards preparedness against. However, the authors also suggested that there is still an enormous scope for improvement, and the existing system is not yet ready for large scale and dynamic situations.…”
Section:  Crisis Mapping Methodsmentioning
confidence: 99%
“…Social media platforms have become increasingly important tools for natural disaster management, with several prominent attributes that have the potential to influence disaster response efforts viz. i) Real-Time Information Sharing (Aramendia et al [26], Beltramone & Gomes [27], Cheong et al [28], Karmegam et al [59], Turay and S. Gbetuwa [68], Zhu et al [66]), ii) Crowdsourced Data Collection (Tavra et al [65], Astarita et al [37]), iii) Two-Way Communication (Tran & Kim [42], Zhang et al [45]), iv) Public Engagement and Mobilization (Malla et al [70], Tarchiani et al [35], Al-Mueed et al [29], Mitcham et al [40]), v) Information Aggregation and Analysis (Malla et al [70], Han & Wang [39], Tavra et al [65]), vi) Crisis Mapping and Visualization (Divjak and Lapaine [47], Du et al [49], Durrant et al [50], Maxant et al [51], Vavassori et al [52]). Under attributes of real-time information sharing, it is believed that social media allows for the rapid dissemination of information during disasters, enabling authorities, organizations, and individuals to share updates on hazards, evacuation orders, shelter locations, road closures, and other important developments in real time.…”
Section: R2: What Is the Currently Dominant Research-based Approaches...mentioning
confidence: 99%
“…The unique nature of each WHS requires the need for tailored DRM strategies that allow CH experts and the WHSM to mould the details of a DRM strategy to fit the needs of the particular WHS. However, allowing for a degree of flexibility in the development and implementation of a DRM may require us to reflect on the highly controlled and pre-defined process of DRM Furthermore, the delivery of DRM is often coordinated at higher levels of governance by governments, ministries and civil protection authorities [9]. This may hinder the degree of flexibility WHSM may have in the design and delivery of a DRM in the drafted phases of the strategy.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Experts have also highlighted the potential harmonisation of CH protection and achieving the 2022 sustainable development goals [7,8]. Another crucial aspect of this paradigm shift is the integration of CH into disaster risk management (DRM) theory and practice [9][10][11][12][13]. The reasoning behind this integration is the perceived vulnerability of CH to the increasing severity and frequency of disaster events as a result of climate change [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Culture and its inclusion in sustainable development has been researched lately, with more people being interested in the topic [1][2][3]. Sustainable development is defined as "development that meets the needs of the present without compromising the ability of future generations to meet their own needs" [4].…”
Section: Introductionmentioning
confidence: 99%